2018
DOI: 10.3389/fphar.2018.00624
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of San-Cao Granule on Con A-Induced Liver Injury in Mice and Mechanisms of Action Exploration

Abstract: Objective: San-Cao granule (SCG), a traditional Chinese herb formula, has been used for treating autoimmune hepatitis (AIH) in our clinics for a long time. However, its active ingredients and mechanisms of action were still unknown due to its complicated chemical compositions. In the present study, the pharmacological study of SCG on acute liver injury induced by Concanavalin A (Con A) was performed to provide a scientific evidence for SCG against liver injury.Methods: In order to screen active components and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…Then, hematoxylin-eosin (HE) staining and Masson staining were used to observe the pathological changes of liver tissue [ 21 , 23 ]. The results of HE showed that the liver tissue structure of the control group was normal without morphological changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, hematoxylin-eosin (HE) staining and Masson staining were used to observe the pathological changes of liver tissue [ 21 , 23 ]. The results of HE showed that the liver tissue structure of the control group was normal without morphological changes.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the effects of AR on the expression of α -SMA, HMGB1, and collagen I in liver tissue of fibrosis rats, immunohistochemical analysis was performed as described previously [ 21 ]. Paraffin sections of liver tissues were put in xylene and gradient ethanol for deparaffinization and dehydration, and then the sections were put into citric acid antigen retrieval solution for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial I/R injury is a complicated pathologic process, and the molecular mechanisms underlying this process remain unclear [11]. β-Sitosterol has been shown to be protective against I/R injury in different disease conditions * * * Evidence-Based Complementary and Alternative Medicine [7,9,10,[12][13][14][15][16]. In the present study, we showed that OGD/ R treatment suppressed cell viability and induced cell apoptosis and ROS production but reduced MMP, and β-sitosterol treatment attenuated H/R-induced cardiomyocyte injury, which was consistent with previous findings showing that β-sitosterol exerted protective actions against oxidant injury in H9c2 cells and rat hearts [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, most of study focused on its cytotoxicity toward tumor cells (7,20). Nowadays, increasing evidence has demonstrated that DHT shows beneficial potentials such as antiinflammation (16,42,43), anti-ischemia/reperfusion (20), antiallergic (21), and hepatoprotective effects (41), while its therapeutic effects on ameliorating vulnerable plaque are poorly studied. Considering this, we investigated the effect of DHT on treating vulnerable plaques and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%